SINERGI ISLAM, TRADISI LOKAL, DAN KETAHANAN BUDAYA DALAM MASYARAKAT JAWA-BETAWI UNTUK MENJAGA TOLERANSI DAN KEADILAN SOSIAL DI JAKARTA. - Baihaqi, Arya; Salma Faiqa, Amanda; Hilmiansyah, Jibran, Windri Novianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The Javanese-Betawi communities in Jakarta demonstrate a harmonious synergy between Islamic values, local traditions, and cultural resilience in addressing the social challenges of a modern urban environment. Religious values such as tolerance, deliberation, and justice are integrated into cultural practices like selametan, social gatherings, and respect for community leaders. This integration not only strengthens collective identity but also serves as a social force that fosters a peaceful and just environment amid diversity. Their cultural resilience is reflected in their ability to preserve tradition while adapting to social change. This study affirms that the combination of spiritual values and local wisdom forms a crucial foundation for building an inclusive and harmonious society in Jakarta. Keywords: Islam, local traditions, cultural resilience, Javanese-Betawi communities, tolerance, social justice, social change, Jakarta